Design of Motor Current Signature Analysis (MCSA) Based on LabVIEW for Online Detection of Induction Motor Faults - Dimas Anton Asfani; Soedibyo Soedibyo; I Made Yulistya Negara; Daniar Fahmi; Muhammad Eko Septiawan; Mochammad Wahyudi; Neisya Islamey Rifma (JAREE (Journal on Advanced Research in Electrical Engineering), 2017)
Induction motor is the most common used electric motor in industry. Along with its operation, induction motor can savere certain damage which is generally dominated by internal fault, such as s rotor fault, stator fault, and bearing fault. In this paper, the online detection based on motor current signature analyses (MCSA) for such faults was designed using LabVIEW. MCSA was performed to obtain the frequency which indicated the presence of certain damage of induction motor. The experimental result showed that the accuracy of proposed method reached 90 %. Keywords: induction motor; online detection; rotor fault; stator fault; bearing fault; MCSA.